2006
DOI: 10.1111/j.1708-8305.2006.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Travel Clinics in Québec (Canada)

Abstract: To continuously improve its assistance to Québec travel health providers, the Québec Advisory Committee on Travel Health conducted an exploratory and descriptive survey of dedicated travel clinics in Québec (Canada). During autumn 2003, a cross-sectional descriptive survey was carried out among the 97 travel health clinics listed in Québec. Data were collected using a self-administered questionnaire sent by mail. The response rate was 94%. More than three quarters of travel clinics in Québec are located in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It is quite clear, however, that travel clinics can only be effective if travelers use them. In Quebec, Canada, there are almost a hundred travel health clinics offering preventive services to travelers for a population of around seven million, but only around 15% of Quebecois travelers who are at risk consult a travel clinic 16 . One study conducted in London found that just 11 HIV-infected individuals sought pre-travel medical consultations 3 and another study in the USA found that only one HIV-infected patient consulted a travel medicine expert before traveling 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is quite clear, however, that travel clinics can only be effective if travelers use them. In Quebec, Canada, there are almost a hundred travel health clinics offering preventive services to travelers for a population of around seven million, but only around 15% of Quebecois travelers who are at risk consult a travel clinic 16 . One study conducted in London found that just 11 HIV-infected individuals sought pre-travel medical consultations 3 and another study in the USA found that only one HIV-infected patient consulted a travel medicine expert before traveling 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In Québec, Canada, there are almost a 100 travel health clinics offering preventive services to travellers for a population around seven million and just about 15% of Québec travellers at risk consult a travel clinic. 9 One study performed in London found that just 11 HIV-infected persons sought pre-travel medical consultation 10 and another one in the USA found that only one HIV-infected patient consulted a travel medicine expert before travel. 11 Experts generally bemoan the low attendance rates in travel clinics and many strategies have been suggested to increase frequency of pre-travel consultation 8 Although many clinicians attending HIV-infected patients are specialists in infectious and parasitic diseases some of them may not feel able to advise a traveller.…”
Section: Introductionmentioning
confidence: 99%